2019
DOI: 10.1186/s12913-019-4410-9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding patients’ satisfaction with physician assistant/associate encounters through communication experiences: a qualitative study in acute hospitals in England

Abstract: Background Physician assistants/associates (PAs) are a recent innovation in acute hospital teams in England and many other countries worldwide. Although existing evidence indicates generally high levels of patient satisfaction with their PA hospital encounters, little is known about the factors associated with this outcome. There is a lack of evidence on the process of PA-patient communication in hospital encounters and how this might influence satisfaction. This study therefore aimed to understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 44 publications
(57 reference statements)
5
18
0
Order By: Relevance
“…[13] Developing an outline of the broadly defined Irish PA scope of practice for a given team could be helpful, serving as something the PAs could "fall back on" if their activity is questioned by staff less familiar with the role. One qualitative study in the UK found that although patient participants had poor understanding of the PA role, they were still generally satisfied with their medical encounter with the PA. [26] Similar findings were shown in an Irish study. [20] PAs in the present study expressed how their patients welcomed care provided by a PA.…”
Section: Discussionsupporting
confidence: 80%
“…[13] Developing an outline of the broadly defined Irish PA scope of practice for a given team could be helpful, serving as something the PAs could "fall back on" if their activity is questioned by staff less familiar with the role. One qualitative study in the UK found that although patient participants had poor understanding of the PA role, they were still generally satisfied with their medical encounter with the PA. [26] Similar findings were shown in an Irish study. [20] PAs in the present study expressed how their patients welcomed care provided by a PA.…”
Section: Discussionsupporting
confidence: 80%
“…Criterion-related validity was ascertained for the overall measure as well as the dimensions in predicting at least 1 of the 3 outcome variables: satisfaction, health bene ts, and health level, which is consistent with previous studies (e.g. 33,34,35). Lastly, a model with a second-order factor, "treatment services", for 4 of the dimensions was proposed based on the results of the validity and reliability analyses: "nurse services", "doctor services", "information", and "organisation".…”
Section: Discussionsupporting
confidence: 72%
“…Patient confusion with new mid‐level practitioner titles and roles has been well documented, 8‐11 alongside evidence that the novel terminology can be difficult to interpret and is sometimes misleading 8,10 . Existing studies in England report poor recognition and comprehension of the PA role among hospital patients 12,13 . They are often confused by the title; its meaning is not immediately obvious and needs explanation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, patients can mistakenly perceive PAs to be doctors and express concerns when made aware of the misconception. To prevent confusion, explanatory patient information about the role was considered necessary and beneficial 13 . A study in the Netherlands, where the role is also unfamiliar, similarly identified that hospital staff thought patients were unaware whether they had seen a PA or doctor 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation